Evaluation of the Anticancer Potential of S. euphratica, S. staminea, and S. trichoclada in Colon Cancer: Monotherapy and Combination with Cisplatin - Sever, Aydın; Erdoğan, Mehmet Kadir; Gündoğdu, Ramazan; Geçibesler, İbrahim Halil and Behçet, Lütfi (Journal of Medical Science, 2025)
Introduction. The use of herbal products in the treatment of colon cancer appears promising. Numerous Salvia species have been identified to exhibit cytotoxic properties. In this study, ethanolic extracts of three Salvia species collected from the Bingöl region (Salvia euphratica, Salvia staminea, and Salvia trichoclada), which have not been sufficiently investigated for their anticancer potential, were applied to the HT-29 colon cancer cell line both as monotherapies and in combination with cisplatin. Material and methods. A crystal violet assay was performed to assess cell viability. Changes in cellular functions were evaluated using colony-formation and 3D soft agar assays for colony-forming ability, wound-healing assays for migration, and Western blot analyses for protein expression levels. Results. The IC₅₀ values were determined as 38.16, 40.85, and 43.40 µg/ml, respectively. In synergy assays with cisplatin, the combination indices were 9.54, 9.37, and 9.61, respectively. It was observed that the Salvia species alone reduced colony-forming ability in both 2D and 3D cultures, whereas this effect diminished when combined with cisplatin. The wound closure percentage decreased under combination treatment. Furthermore, although mTOR and AKT protein levels were reduced in combination treatments compared with monotherapy, p53 and c-PARP levels were elevated. Conclusions. Although the examined Salvia species exhibited strong cytotoxic effects when used alone, these effects were attenuated when combined with cisplatin. Further investigations are needed to elucidate the underlying mechanisms of this phenomenon.